Rekonstruksi Nilai Siri’ Na Pacce dalam Pembentukan Dinasti Politik Yasin Limpo - Sofyandi F, Aqsa Gautama; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2019)
Abstract Siri’ Na Pacce is a phillosophical value of South Sulawesi people. As a Socio-cultural value that ordered, this value comes with the positive falue as to enpower the dignity of the solidarity & solidity, meanwhile this value tends to being collusive and making a nepotism. This value is used by Yasin Limpo’s Dynasty to legitimating their power to hegemony of power in South Sulawesi. This research title is “Reconstruction of Siri’ Na Pacce Value In The Establishment of Yasin Limpo’s Dynasty” aimed to described the movement of Yasin Limpo’s Dynasty that using Siri’ Na Pacce Value as a Patron Client. This Research Using Descriptive-Qualitative methods with Deep Interview. The Based Theory that used in this research is Cultural-Rational Choice Theory and Twilight Institution Theory that described legitimation of power within the Twilight by Yasin Limpo Dynasty under the power of Adnan Purichta with the case of LAD no.05 2016 Year. Key Word: Siri’ Na Pacce, Political Dynasty, Yasin Limpo